Top corporate brands and the global structure of country brand positioning: An AutoCM ANN approach. (30th December 2016) - Ferilli, Guido; Sacco, Pier Luigi; Teti, Emanuele; Buscema, Massimo
Highlights: We develop an ANN-based approach to the analysis of country and top corporate brands. We find that Germany is the hub in the global MST positioning of country brands. We find that the USA is marginally positioned in the same global MST. We reconstruct the global topology of MST country positioning. Abstract: Working on the top 100 Interbrand world corporate brands dataset over the 10-years period 2001–10, we analyze the relative positioning of country brands as derived from the structural characteristics of the corresponding portfolios of top corporate brands. We find that the structural complexity of both sector and country variables are not correlated with brand equity. Moreover, we apply an innovative ANN methodology, AutoCM, to build the Minimum Spanning Tree (MST) of the multi-dimensional similarities among the top corporate brands structures at country level, and carry out a further related analysis in terms of the so called Maximum Regular Graph (MRG). We find that while the USA dominates the ranking of top brands at a global level, it does not have a central positioning in the MST and MRG, whereas Germany and other European and Far-Eastern countries do. We show how these results may have significant implications for the strategic intelligence analysis of country and corporate brands, and of their inter-relatedness. Moreover, we illustrate how AutoCM qualifies as a new computational approach that usefully expands the toolbox of scholars and analysts in corporate and country branding in a relevant, as yet unexplored direction.